2020
DOI: 10.1123/jmpb.2019-0064
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Energy Expenditure and Step Count Measured by ActiGraph Accelerometers Among Dominant and Nondominant Wrist and Hip Sites

Abstract: Objective: To validate and compare the accuracy of energy expenditure (EE) and step counts measured by ActiGraph accelerometers (ACT) at dominant and nondominant wrist and hip sites. Methods: Thirty young adults (15 females, age 22.93 ± 3.30 years) wore four ActiGraph wGT3X accelerometers while walking and running on a treadmill for 7 min at seven different speeds (1.7, 2.5, 3.4, 4.2, 5.0, 5.5, and 6.0 mph). The EE from each ACT was calculated using the Freedson Adult equation, and the “worn on the wrist” opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…It has been suggested that users may assume that the “Worn on wrist” option in ActiLife would provide more accurate PA estimates (Mueller et al, 2020 ). However, as was analyzed, our results and those of other authors warn about the accuracy of the estimates (McMinn et al, 2013 ; Mandigout et al, 2019 ; Mueller et al, 2020 ; Nuss et al, 2020 ). In this context, it is noteworthy that the use of wrist correction factors will likely decrease as new wrist-based algorithms are developed.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…It has been suggested that users may assume that the “Worn on wrist” option in ActiLife would provide more accurate PA estimates (Mueller et al, 2020 ). However, as was analyzed, our results and those of other authors warn about the accuracy of the estimates (McMinn et al, 2013 ; Mandigout et al, 2019 ; Mueller et al, 2020 ; Nuss et al, 2020 ). In this context, it is noteworthy that the use of wrist correction factors will likely decrease as new wrist-based algorithms are developed.…”
Section: Discussionsupporting
confidence: 59%
“…The same PA indices (EE, MVPA%, steps/minute, and VM CPM) were calculated for hip and wrist records. Similar to previous studies, according to the manufacturer's recommendations, for wrist-worm data, the “Worn on wrist” option (ActiLife software) was selected during data scoring (McMinn et al, 2013 ; Mueller et al, 2020 ; Nuss et al, 2020 ; Guediri et al, 2021 ). When that option is selected, ActiLife software applies “piece-wise scaling” to the collected data, enabling direct comparison between PA indices (e.g., EE) obtained from hip and wrist measurements (ActiGraph, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations